The effect of Driver's model on learning some basic volleyball skills for students - Abdel-Nabi , Noor Al-Huda; Daoud, Suzan (Journal of Physical Education, 2023)
The study aimed to identify the effect of Driver's model on learning the skills subject of the research. As for the research hypothesis, there are statistically significant differences between the results of the cardio and post-test for the control and experimental groups in learning to perform some volleyball skills. The two researchers used the experimental research method using the method of the experimental and control groups. The research sample consisted of (10) groups of students in the second stage, where (3) groups were chosen, namely (H, Z, and Y), as the researcher chose section (J) for the exploratory experiment, and the number of them was large. (33) and Section (E), the experimental group (Driver’s model) and Al-Bala’, numbered (28), and Section (G), the control group and Al-Bal’, numbered (30). After that, the two researchers chose the research variables, performance evaluation tests, conducting exploratory experiments, and developing exercises through Driver’s model, and they also conducted tests. Pre and post to obtain the results, process them statistically, and then extract the results. Through the latter, the two researchers concluded: Using an educational model based on a sequence and application interspersed with an arrangement leads to learning volleyball skills. And introducing the educational model proposed by the two researchers into teaching volleyball skills